Factors influencing the consumption of Jiaogulan herbal tea in Phayao Province, Northern Thailand: 10.55131/jphd/2025/230116 - Sakulwattana, Wannita; Seangpraw, Katekaew; Kantow, Supakan; Sukhabot, Karnchanok; Jaengpromma, Pongnared; Ong-Artborirak, Parichat (Journal of Public Health and Development, 2024)
Tea is a popular beverage that has experienced increased consumption due to its health benefits and cultural significance. This study aimed to examine Jiaogulan herbal tea consumption and its association with information sources in Phayao Province, Northern Thailand. The study also employed the Theory of Planned Behavior (TPB) as a framework to investigate Jiaogulan consumption behaviors. We conducted a cross-sectional study in Phayao Province that included 404 individuals aged 20 and above. The sample was selected using convenience sampling, and data were collected through a self-administered questionnaire. Approximately 25.7% of participants consumed Jiaogulan herbal tea in the three months prior to the study, and 32% had received information about its health benefits. Adjusted binary logistic regression analysis indicated a significant association between Jiaogulan tea consumption and receiving information from family members (AOR = 3.85, 95% CI = 1.58–9.42) and the internet (AOR = 3.44, 95% CI = 1.83-6.46). Among Jiaogulan herbal tea consumers, Spearman’s rank correlation test showed a significant correlation between attitude and subjective norms (rs = 0.377, p<0.001), and between subjective norms and Jiaogulan consumption behavior (rs = 0.220, p=0.025). The results indicate that the TPB framework effectively predicts factors influencing the consumption of Jiaogulan herbal tea products. To promote tea consumption, efforts should be made to prioritize improving community knowledge and the public’s understanding of herbal tea’s health benefits.